A Review of "Things I Wish I Knew as a Teacher: Reflections of a Retired Principal" By Robert Hamilton (2021) - Nathan Rickey; Katrina Carbone; Yasmine Dannawy; Stephen MacGregor (Canadian Society for Studies in Education, 2022)
Not applicable for book reviews, according to CJNSE "Author Guidelines."